Elements of Open Education: An Invitation to Future Research - Zawacki-Richter, Olaf; Conrad, Dianne; Bozkurt, Aras; Aydin, Cengiz Hakan; Bedenlier, Svenja; Jung, Insung; Stöter, Joachim; Veletsianos, George; Blaschke, Lisa Marie; Bond, Melissa; Broens, Andrea; Bruhn, Elisa; et al. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2020)
This paper explores elements of open education within the context of higher education. After an introduction to the origins of open education and its theoretical foundations, the topics of open and distance learning, international education issues in open education, open educational practices and scholarship, open educational resources, MOOCs, prior learning accreditation and recognition, and learner characteristics are considered, following the framework of macro, meso, and micro levels of research in open and distance learning. Implications for future research at the macro, meso, and micro levels are then provided.